Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/brb3.1198
|View full text |Cite
|
Sign up to set email alerts
|

Positive affective priming decreases the middle late positive potential response to negative images

Abstract: IntroductionThis study aims to expand on previous literature showing that incidental emotion state priming in a specific domain leads to a higher probability that the primed emotion domain will be activated during a subsequent task.MethodsTo that end, we investigated the influence of happy, fearful, and neutral incidental emotion state priming on subsequent responses to emotionally negative and neutral pictures, measured by the event‐related potential (ERP) late positive potential (LPP). New to our study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Then, the nine-point SAM scale ranging from 1 ( unpleasant facial expression ) to 9 ( pleasant facial expression ) was presented for 3 seconds, at which time the participants rated the emotional valence of the images by responding with the keyboard, which was considered one trial. We designed the study protocol based on previous studies (Aguado et al, 2019; Cheng et al, 2017; Hill et al, 2019). Completion of a block of trials required 4–5 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, the nine-point SAM scale ranging from 1 ( unpleasant facial expression ) to 9 ( pleasant facial expression ) was presented for 3 seconds, at which time the participants rated the emotional valence of the images by responding with the keyboard, which was considered one trial. We designed the study protocol based on previous studies (Aguado et al, 2019; Cheng et al, 2017; Hill et al, 2019). Completion of a block of trials required 4–5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, there was no significant difference in N1, P2, and N2 amplitudes for happy moods. Hill et al (2019) examined the effect of mood (happy/neutral/fear) induced by movies on emotional evaluation by measuring the LPP in response to unpleasant images. They demonstrated that the LPP amplitude increased significantly more for unpleasant images than for neutral images when participants were in neutral and fearful moods but not in happy moods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous studies ( Larson et al, 2014 ; Hill et al, 2019 ) and the visual inspection of grand-averaged waveforms and scalp topographies in the present study, the P2, N2, N450, frontal LPP, and the parietal LPP (analyzed separately at early and middle latency ranges) were analyzed. The peak amplitudes of the P2 in the time window of 150–200 ms, N2 in the time window of 190–350 ms, and the mean amplitudes of the N450 in the time window of 400–600 ms and frontal LPP in the time window of 700–900 ms were extracted at electrodes at the frontal and frontal-central areas (i.e., F3, Fz, F4, FC3, FCz, and FC4).…”
Section: Methodsmentioning
confidence: 99%